The Safety Road and Volunteer of Traffic Accident Prevention in Chaiyaphum Province - Palaphon, Chookait; Intaraprajob , Inthuraporn; Chanphong, Somsak (Journal of Modern Learning Development, 2021)
The objectives of this research were 1) to collect and study the condition and problems of accidents in the community; 2) to take lessons/analyze the guidelines for solving accidents in the community The target group includes volunteer village pilots participating in the Road Safety Project. Na Fai Ruamjai Community Prevent traffic accidents in 5 villages and act as a leader in coordinating with people in the area who have an attitude that wants to develop traffic accident prevention in the community, consisting of totaling 15 people, which were obtained by choosing from 15 people willing to participate in the project (purposive sampling). The research tools were 1) 1 questionnaire 2) One survey and 3) one interview form, and 4) Questions for the lesson transcript. data analysis using basic statistics (mean, standard deviation) and content analysis. The results of the research found that 1. Conditions and problems of accidents in the community From the data collection, it was found that the nature of the accident The Ban Na Fai community was at a severe level. The accident that occurred was a collision. There were severe injuries and in some cases death, and found that there are 5 areas at risk of accidents for people and students of Na Fai Subdistrict, and differ according to the date and time: 1) in front of Chaiyaphum Rajabhat University (The entrance to the university) 2) At the back door of Chaiyaphum Rajabhat University (back door of the university) 3) at the junction to Ban Na Fai 4) at the Huai Chan intersection and 5) at the junction to the Choraka Reservoir cause of accident Data were collected using survey, observation, interview and dialogue methods. The group can summarize the causes of accidents into 2 main causes, which can be divided into Causes are caused by physical conditions on the road and caused by driving behavior of road users. 2. Guidelines for solving accident problems in the community according to the accident area 5 points: 1) in front of Chaiyaphum Rajabhat University (The entrance to the university) 2) At the back door of Chaiyaphum Rajabhat University 3) Around the junction to Ban Na Fai 4) At the Huai Chan Intersection and 5) Around the junction to the Choraka Reservoir From the discussion to extract lessons/analyze approaches to solving accidents in the community, divided into 2 approaches, one that can be done immediately; and the guidelines cannot be implemented immediately. An immediate solution to the problem is providing the security officers of the university Help drain the car in front of the university in the morning and evening. The solution to the problem that cannot be done immediately is training to cultivate awareness and correct actions such as Training on traffic rules for students Organizing a driver's license test for students within the university Training on traffic knowledge for the public and new students during the freshman year and a solution that requires coordination in fixing the university's security officers to help drain the car in front of the university Universities have established rules regarding student wearing helmets. Adjusting the scenery of the island in the middle of the road Having a patrol patrolling driving, if a student breaks traffic rules, points may be deducted. Adding a longer island in the middle of the road to narrow the turning point Solving this problem will require coordination. for the police to tighten traffic discipline to increase the safety of driving because those who use the road will be more careful in using the car. This approach can be defined as a strategy 3 Rama 3 P. is a strategy in operation. To be a guideline for solving accidents in the community, namely 3 schools to recognize, initiate campaigns and 3 years to coordinate safety practices.